Apolipoprotein E genotyping in the Malay, Chinese and Indian ethnic groups in Malaysia - a study on the distribution of the different apoE alleles and genotypes - Seet, W.T.; Tan, J.A.M.A.; Yen, T.S. (2004)
Background: Apolipoprotein E (apoE) is encoded by a polymorphic gene located on chromosome 19. The three common apoE alleles are epsilon2, epsilon3 and epsilon4. We studied the frequencies of the apoE alleles and genotypes in the three ethnic groups-Malay, Chinese and Indian-in Malaysia using DNA amplification followed by agarose gel electrophoresis. Methods: EDTA blood was collected and DNA was extracted using proteinase K-SDS digestion and purified by phenol-chloroform extraction. The apoE gene sequence was amplified using the PCR and apoE genotyping was performed by restriction enzyme digestion with HhaI. Results: Genotyping of the apoE gene produces six genotypes-E2/E2, E2/E3, E3/E3, E2/E4, E3/E4 and E4/E4. The most common apoE genotype in the Malays, Chinese and Indians studied was ENE3, thus the most common apoE allele was epsilon3. The three common apoE genotypes were E3/E3 followed by E3/E4 and E2/E3, except in the Indians where E2/E3 was not detected. The three apoE alleles were confirmed in the Malays, Chinese and Indians except for the e2 allele which was absent in the Indians. Conclusion: The combined frequency of the apoE alleles in the Malays, Chinese and Indians was 0.058, 0.829 and 0.114 for epsilon2, epsilon3 and epsilon4, respectively. (C) 2003 Elsevier B.V. All rights reserved.